Peran KORPRI dalam Perlindungan Hukum bagi PNS - Khairil Anwar; Nabila Nabila; Nurhayati Nurhayati; Rizqi Nurhidayani (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This research aims to find out the role of Korpri in providing legal protection for civil servants. Philipus M. Hadjon stated that legal protection for the community is a government action that has a preventive and responsive nature, the preventive nature has the aim of preventing disputes which directs government action to be careful in making decisions based on discretion and protection, while The responsive nature aims to prevent disputes from occurring, including handling them in judicial institutions. This research is a type of normative research with literature study. The results of the research show that Korpri's role in providing legal assistance to civil servants is carried out through LKBH KORPRI. This is in accordance with the ASN Law which states that in Article 21 Letter d and Article 22 Letter c of Law no. 5 of 2014 civil servants have the right to obtain protection and in Article 92 paragraph (1) Letter d and Article 106 paragraph (1) Letter e it is explained that the government also has an obligation to provide legal protection in the form of legal assistance.